Registration of 'AG18' peanut. Issue 3 (8th September 2021) - Baring, Michael R.; Cason, John M.; Burow, Mark D.; Simpson, Charles E.; Chagoya, Jennifer; Bennett, Brian D.
Abstract: 'AG18' (Reg. no. CV‐147, PI 698186) is a high‐yielding, high‐grading, high‐oleic fatty acid, runner‐type peanut ( Arachis hypogaea L. ssp. hypogaea var. hypogaea ) cultivar with good resistance to Sclerotinia blight (caused by Sclerotinia minor Jagger). The cultivar was developed by the Texas A&M AgriLife Research peanut breeding program to provide growers with a higher‐yielding option when compared to the previously released 'Tamrun OL11' cultivar. AG18 was tested under the experimental designation of Tx121082 and was released in 2020. It maintains the high percentage of total sound mature kernels that Tamrun OL11 had, as well as the resistance to S. minor . However, it proved to have higher yield potential across environments and years than did Tamrun OL11. Additionally, the seed size of AG18 is smaller than that of Tamrun OL11 and closer to the past industry standard, 'Florunner', making it more attractive to manufacturers. Core Ideas: AG18 is a high‐yielding high‐grading runner peanut cultivar. AG18 is a high oleic runner peanut cultivar well suited for west Texas. AG18 has good Sclerotinia resistance comparable to Tamrun OL11. AG18 has a roasted peanut flavor similar to Tamrun OL11. Fat and sugar percentages are not statistically different from Tamrun OL11.